Profiles of exercise dependence symptoms in Ironman participants. (May 2016) - Magee, Christopher A.; Buchanan, Ian; Barrie, Lance
Abstract: Objective: To identify distinct profiles of Ironman participants based on levels of exercise dependence, and examine whether these profiles differed in relation to eating patterns and psychological distress. Design: Cross-sectional survey study of 345 Ironman participants in Australia. Main outcome measures: Exercise dependence symptoms were assessed via the Exercise Dependence Scale. Eating patterns were assessed via the three-factor eating questionnaire, and psychological distress measured using the Kessler 6 scale. Results: Latent profile analysis identified five distinct profiles based on responses to the Exercise Dependence Scale, which were labelled: Asymptomatic; Time Committed; Low psychological dependence; Symptomatic; and At-risk. The At-risk and Symptomatic profiles had less healthy eating patterns and higher psychological distress compared with the other profiles. Conclusions: These findings suggest important individual differences in the nature and severity of exercise dependence symptoms in Ironman participants. The majority of Ironman participants appeared to have a healthy involvement with Ironman. However, approximately 30% of Ironman participants belonged to the At-risk and Symptomatic profiles, which could reflect maladaptive patterns of exercise. Highlights: Exercise dependence has rarely been investigated in Ironman participants. We identified five distinct profiles of exercise dependence in Ironman participants. Profiles differed in relation to eating patterns and psychological distress.